Rate and breadth of protein evolution are only weakly correlated - Naumenko, Sergey A (BioMed Central, 2012)
BACKGROUND: Evolution at a protein site can be characterized from two different perspectives, by its rate and by the breadth of the set of acceptable amino acids. RESULTS: There is a weak positive correlation between rates and breadths of evolution, both across individual amino acid sites and across proteins. CONCLUSIONS: Rate and breadth are two distinct, and only weakly correlated, characteristics of protein evolution. The most likely explanation of their positive correlation is heterogeneity of selective constraint, such that less functionally important sites evolve faster and can accept more amino acids. REVIEWERS: This article was reviewed by Eugene V. Koonin, Arcady R. Mushegyan, and Eugene I. Shakhnovich.